Strengthening reading competences from the reading tree strategy. - Sierra Villamil, Nathalia Lizeth (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Reading from education is determined as a teaching and learning strategy, necessary for everyday life, since it develops in people critical thinking, from the classroom it provides in children spaces of socialization, strengthen your creativity and imagination and develop your ability to think clearly. For this reason, this classroom pedagogical project proposes to strengthen reading skills through the strategy of the reading tree in the students of the primary section of the “Military School Coronel Fray Jose Ignacio Mariño”. In addition, three pedagogical workshops were carried out as a strategy that made it easier to meet the proposed objectives, once the results were analysed. It can be concluded, the importance of the teacher as a facilitator of spaces that contribute to promoting reading as a habit and to training competent readers capable of organizing ideas and assuming a critical position.